Interaction between Bacillus cereus and Cultured Human Enterocytes: Effect of Calcium, Cell Differentiation, and Bacterial Extracellular Factors - Minnaard, Jessica (2013)
Bacillus cereus interaction with cultured human enterocytes and the signaling pathways responsible for the biological effects of the infection were investigated. Results demonstrate that calcium depletion increases the ability of strains T1 and 2 to invade cells. Bacteria associated in greater extent to undifferentiated enterocytes and extracellular factors from strain 2 increased its own association and invasion. Inhibitors of signaling pathways related to phosphorylated lipids (U73122 and wortmannin) were able to significantly reduce cytoskeleton disruption induced by B. cereus infection. Adhesion of strain T1 decreased in the presence of U73122 and of wortmannin, as well as when those inhibitors were used together. In contrast, invasion values were diminished only by U73122. Results show that different factors are involved in the interaction between B. cereus and cultured human enterocytes. Following infection, disruption of the cytoskeleton could facilitate invasion of the eukaryotic cells.